A Case Study of the Head CT Scan Procedure in Pediatric Patients with Clinical Hydrocephalus at Hospital X Ponorogo - Dewi, Hanifa Larasati; Nasokha, Ildsa Maulidya Mar’athus; Utami, Asih Puji (Jurnal Biologi Tropis, 2025)
Hydrocephalus is a common congenital abnormality in pediatric patients, characterized by ventricular enlargement due to the accumulation of cerebrospinal fluid (CSF). However, variations in handling, parameters, and radiation protection exist among hospitals, necessitating further evaluation. This study aims to analyze the head CT scan procedure in pediatric patients with clinical hydrocephalus. This study employed qualitative case study design involving a 7-month-old pediatric patient with an indication of hydrocephalus. Data were obtained through observation and interviews with three radiographers and one radiology specialist, as well as from secondary sources. The hospital’s examination procedure included general preparation, positioning the patient supine (head first), and no sedation was performed. Technical parameters used the default settings of the machine, 120 kV, 140 mAs, slice thickness of 5 mm, and reconstruction slice of 1.25 mm, for both pediatric and adult patients. Radiation protection was applied only to the patient’s companion, while the patient dose was monitored by the CT system. Radiographic findings indicated obstructive hydrocephalus with a cystic lesion, with the underlying cause identified as Dandy–Walker malformation. In conclusion, pediatric head CT scan procedures were performed according to basic standards. However, the use of standard parameters and limited radiation protection indicate a need for improvement. It is recommended to implement protocols tailored to the patient's age and clinical condition, and optimize radiation protection according to the ALARA principle, to improve examination quality and patient safety.